The determinants of inflation differentials in the euro area - Laura Moretti (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
Inflation differentials in the euro area have been persistent since the adoption of the single currency. This paper analyzes the impact of product and labor market regulation on inflation in a sample of 11 countries. The results show that, after the adoption of the euro, product market deregulation has a relevant and significant effect on the level of inflation, while higher labor market regulation increases the responsiveness of inflation to the output gap.
Keywords: E31; E58; E65; L51; 330; Labor Market Deregulation; Product Market Deregulation; EMU; Inflation Rate